Estimated need for anthelminthic medicines to control soil-transmitted helminthiases in school-aged children, 2020-2030 - Chiara Marocco; Fabrizio Tediosi; Mathieu Bangert; Denise Mupfasoni; Antonio Montresor (BMC, 2020)
Abstract Background Soil-transmitted helminthiases (STH) are part of the group of neglected tropical diseases traditionally treated with preventive chemotherapy interventions. In recent years, drug donations have been essential to expanding preventive chemotherapy and achieving progressive control of morbidity from STH. This study aims to evaluate the need for anthelminthic medicines during 2020-2030. Methods To estimate the need for anthelminthic medicines, we considered three different scenarios: (1) the control programmes continues to expand coverage and maintains the frequency of drug administration established at baseline; (2) the programmes continues to expand coverage but adapts the frequency of drug administration when the STH prevalence is reduced and (3) the STH programme becomes self-sustainable in some endemic countries. Results We estimate that the number of anthelmintic medicines needed to treat school-aged children will increase by 40% by 2025 and by 52% by 2030 if countries do not change the frequency of preventive chemotherapy (scenario 1); that the number of tablets needed will reduce by 32.4% by 2025 and by 49.1% in 2030 if endemic countries reduce the frequency of preventive chemotherapy (scenario 2); and drug donations could be reduced by 54.4% by 2025 and 74.4% by 2030 if some endemic countries could become independent in drug procurement (scenario 3). Conclusions The number of anthelmintic medicines needed to achieve elimination of morbidity due to STH in school-aged children will decline during 2020-2030. The decline will be substantial if a number of "upper-middle income" countries in which STH are endemic procure, as expected, anthelminthic medicines independently.